Pemberdayaan Tenaga Honorer Pada Bagian Keuangan Kantor Pusat Universitas Sam Ratulangi - Pangalila, Silvana AB (JURNAL ILMIAH SOCIETY, 2015)
Finance Division Headquarters Sam Ratulangi University has the responsibility to work in the financial management of operational support work in both the revenue and expenditure in the financial by fourteen honorary workers. But the execution of the work contract officers confronted a lot of work on the implementation of exceeding hours of work , are not provided with the training , the lack of support means of supporting employment , work does not match the job description , frequent transfer of jobs from permanent employees . This fact clearly indicates undescribed empowerment carried out by elements of leadership and organization to the temporary employees . By him this study aims to analyze the causes have not progressed empowerment of temporary employees. The study concluded that the cause has not progressed empowerment honorary staff in the Finance Department Headquarters Sam Ratulangi University because it is not the function of enabling, facilitating, consulting, collaborating, mentoring and supporting of the elements of leadership as the party who perform the function of empowering the temporary employees are empowered. By it needs to make improvements through the provision of training in financial management for the field work in both pre-employment and a way to involve the training activities carried out by institutions, complementary means of employee by way of structuring the workspace, increase the number of computer and move the file documents / asrip finance, sanction civil servants who deliberately delegate work that is beyond the authority of the honorary workers and facilitate labor fees for menjadaptkan salary according to standard provincial minimum wage, overtime and fight for the benefits of other health insurance.Â Keywords : Empowerment, Honorary Staff, Finance